Clinical & epidemiological significance of Kyasanur forest disease - Munivenkatappa, Ashok; Sahay, Rima; Yadav, Pragya; Viswanathan, Rajalakshmi; Mourya, Devendra (Indian journal of medical research (New Delhi, India : 1994), 2018)
Kyasanur forest disease (KFD) is a known viral haemorrhagic fever in India, for the last 60 years. However, in recent years, the change in epidemiological profile of the disease has suggested that it is now time to consider KFD as an emerging tropical disease in India. The preference should be to educate not only the villagers where it is being reported or detected but also to public health experts, veterinarians, forest officials and medical professionals to pay attention while seeing a patient overlapping with endemic diseases such as Japanese encephalitis, West Nile, dengue, chikungunya, malaria and tuberculosis. Although the existence of KFD is known for a long time, updated understanding of its clinical profile in humans is still limited. This article describes in detail the clinical presentation of KFD reported till date. It also highlights geographical distribution of the disease, risk factors for virus transmission, biochemical/haematological findings and control measures. There is an urgent need for research on KFD, particularly for understanding biphasic nature of illness, development of cost-effective diagnostic tools, utility of non-invasive samples for diagnosis and development of new vaccines.